A Super Tough, Rapidly Biodegradable, Ultrafast Hemostatic Bioglue. Issue 10 (20th January 2023) - Wang, Hufei; Cheng, Junyao; Sun, Feifei; Dou, Xueyu; Liu, Jianheng; Wang, Yiru; Li, Ming; Gao, Jianpeng; Liu, Xiao; Wang, Xing; Yang, Fei; Zhu, Ziran; et al.
Abstract: Death happening due to massive hemorrhage has been involved in military conflicts, traffic accidents, and surgical injuries of various human disasters. Achieving rapid and effective hemostasis to save lives is crucial in urgent massive bleeding situations. Herein, a covalent cross‐linked AG‐PEG glue based on extracellular matrix‐like amino‐gelatin (AG) and PEG derivatives is developed. The AG‐PEG glue gelatinizes fast and exhibits firm and indiscriminate close adhesion with various moist tissues upon being dosed. The formed glue establishes an adhesive and robust barrier to seal the arterial, hepatic, and cardiac hemorrhagic wounds, enabling it to withstand up to 380 mmHg blood pressure in comparison with normal systolic blood pressure of 60–180 mmHg. Remarkably, massive bleeding from a pig cardiac penetrating hole with 6 mm diameter is effectively stopped using the glue within 60 s. Postoperative indexes of the treated pig gradually recover and the cardiac wounds regrow significantly at 14 days. Possessing on‐demand solubility, self‐gelling, and rapid degradability, the AG‐PEG glue may provide a fascinating stop‐bleeding approach for clinical hemostasis and emergency rescue. Abstract : A new bioglue is composed of amidated‐gelatin and Tetra‐PEG‐SS for rapid hemostasis in massive hemorrhage. The amino terminals in gelatin quickly react with active ester moieties in the PEG‐SS, endowing the amino‐gelatin‐PEG glue firm and indiscriminate adhesion with various moist tissues (e.g., adhesively sealing cardiac hemorrhagic wounds). The bioglue provides a fascinating hemostatic approach for clinical hemostasis and emergency rescue.